QUANDO A IMAGEM NECESSITA DA PALAVRA: REFLEXÕES SOBRE A POÉTICA DA ÉCFRASE NO EPIGRAMA LATINO | WHEN THE IMAGE NEEDS THE WORD: REFLECTIONS ON THE POETICS OF EKPHRASIS IN THE LATIN EPIGRAM - Mattiacci, Silvia; Amarante, José; Ambrosio, Renato (Estudos Linguísticos e Literários, 2019)
Este artigo se centra em alguns epigramas de Marcial (7, 84; 9, 76; 10, 32; 1, 109; 9, 43-44) e Ausônio (epigr. 12; Biss. 5; epigr. 11 Green) com o objetivo de refletir sobre a relação complexa entre arte e texto. Os exemplos selecionados destacam as estratégias com as quais o epigrama ecfrástico pretende apresentar-se não como o pálido reflexo do poder de uma imagem, mas como um produto criativo e competitivo que expressa algo que a imagem visual não consegue expressar. Abstract: This article focuses on some epigrams by Martial (7.84; 9.76; 10.32; 1.109; 9.43- 44) and Ausonius (epigr. 12; Biss. 5; epigr. 11 Green) with the aim of reflecting on the complex relationship between art and text. The examples selected highlight the strategies with which ekphrastic epigram intends to present itself not as the pale reflection of the power of an image, but as a creative and competitive product expressing something that visual image cannot express. Keywords: Ekphrastic epigram; Martial; Ausonius; Art/text.